Digitization in records magament at Makassar District Court - Anas, Ali; Mustafa, Delly; Tompo, Natsir; Dhani, Arung; Nurhaedah, Nurhaedah (Junal Ilmu Manajemen, 2024)
This research aims to improve the performance of public services through digital-based archiving. Providing convenience in providing access to information more quickly and measurably with the support of facilities and infrastructure. The research uses qualitative by descriptively describing the phenomenon at the Makassar High Court accurately and systematically, actually and accurately according to the facts then starting with the data collection process, explaining and objectively analysing the research results. Data collection methods through observation, interviews and documentation then data analysis techniques are carried out through data coding to sort and select data according to the type of research and also the characteristics of the research variables then the data is given an explanation in accordance with the meaning and finally drawing conclusions. The results showed that the digital-based archive management system has improved the performance of the Makassar City District Court, reduced administrative complexity, and provided easier access to the parties involved in the legal process. The implication of this research is that investment in digital archive technology is an important step in improving the effectiveness of the Makassar City District Court and public services of the Makassar City District Court.